Covered stents may provide extra protection during carotid artery stenting in high risk patients with an excessive thrombus burden. (31st July 2013) - Tatli, Ersan; Barutcu, Ahmet; Gazi, Emine; Gunduz, Yasemin
Abstract : Carotid artery disease is an important cause of mortality and morbidity related to atherosclerosis. Recently, percutaneous intervention procedures have been widely used to treat atherosclerotic carotid artery disease. We report the case of a 57-year-old male patient with a history of acute amaurosis fugax. Carotid angiography was performed as blood pressure differed between his left and right arms and there was a pan-systolic murmur on the left common carotid artery. Total occlusion of the proximal right brachiocephalic artery and a thrombus occluding 90–99% of the left internal carotid artery were detected by carotid angiogram. A self-expanding graft-covered stent was successfully implanted and there were no complications. This case shows that graft-covered stents may be a good alternative technique in special situations.